A kind of adsorption material and its preparation method and application
By forming a porous network structure of La2O2CO3 and carbon on carbon aerogel, an adsorption material that efficiently adsorbs phosphate is prepared, which solves the problems of poor adsorption capacity and slow rate of traditional adsorbents, and effectively removes phosphate in water and prevents Water is eutrophied.
Patent Information
- Application Number
- CN202410939270.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-07-12
AI Technical Summary
Traditional phosphorus removal adsorbents have problems with poor adsorption capacity and slow adsorption rate, making it difficult to effectively treat phosphorus-containing wastewater, resulting in eutrophication of water bodies and the occurrence of algae blooms.
Adsorption materials including carbon aerogel and a porous network formed on its surface or pore channels, the porous network components are La2O2CO3 and carbon, and are prepared by hydrothermal carbonization, vacuum freeze-drying and lanthanum salt alcohol solution impregnation and calcination to form high efficiency. Adsorbent material for adsorbing phosphate.
The adsorbent material can achieve a removal rate of 99.7% in 25 minutes, has a high adsorption capacity and a fast adsorption rate. It is suitable for the treatment of low-concentration phosphorus-containing waste liquid, significantly improving the water purification effect.
Smart Images

Figure CN118767872B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to an adsorption material and a preparation method and application thereof. Background Art
[0002] Phosphorus is one of the basic substances involved in the biochemical cycle of the earth. It is a nutrient element necessary for the growth of most plants and plays an extremely important role in contemporary industry and agriculture. With the widespread use of phosphorus, its damage to the environment has become increasingly prominent. For example, directly discharging phosphorus-containing wastewater into lakes and rivers will stimulate the growth of algae, cause eutrophication and produce algal blooms, and seriously harm the aquatic ecosystem. In order to prevent eutrophication of water bodies, it is necessary to treat phosphates in water bodies. At present, the methods for removing phosphorus from phosphorus-containing wastewater generally include chemical precipitation, biological methods, membrane separation and adsorption methods. Among them, the adsorption method has the advantages of simplicity, non-toxicity, low adsorbent cost and high efficiency. It is widely used in the recovery of low-concentration phosphorus-containing wastewater and large-scale sewage treatment. Traditional phosphorus removal adsorbents mainly include metal oxides / hydroxides, activated carbon, natural minerals, etc.; these traditional adsorbents have problems such as poor adsorption capacity and slow adsorption rate. Therefore, it is necessary to study and develop phosphorus removal adsorption materials with good adsorption performance. Summary of the invention
[0003] In view of this, the present invention provides an adsorption material and a preparation method and application thereof. The adsorption material provided by the present invention has a high adsorption rate and adsorption capacity for phosphate and can efficiently adsorb phosphate in wastewater.
[0004] In order to solve the above technical problems, the present invention provides an adsorption material, including a carbon aerogel and a porous network formed in situ on the surface and / or in the pores of the carbon aerogel, wherein the components of the porous network are La 2 O 2 CO 3 and carbon.
[0005] Preferably, the La 2 O 2 CO 3 The mass percentage of La in the adsorption material is 40 to 80%.
[0006] Preferably, the pore size of the porous network is 10 to 20 nm.
[0007] The present invention also provides a method for preparing the adsorbent material described in the above technical solution, comprising the following steps:
[0008] The biomass raw material is hydrothermally carbonized to obtain a biochar hydrogel;
[0009] The biochar hydrogel is subjected to vacuum freeze drying to obtain a carbon aerogel;
[0010] The carbon aerogel is immersed in an alcohol solution of a lanthanum salt for adsorption and then calcined to obtain the adsorption material.
[0011] Preferably, the biomass raw material includes peel;
[0012] The temperature of the hydrothermal carbonization is 170-190° C., and the time is 10-14 hours.
[0013] Preferably, the vacuum degree of the vacuum freeze-drying is 5 to 15 Pa; the temperature of the vacuum freeze-drying is -60 to -40°C; and the time of the vacuum freeze-drying is 24 to 72 hours.
[0014] Preferably, the lanthanum salt comprises hydrated lanthanum nitrate, hydrated lanthanum chloride, hydrated lanthanum carbonate or hydrated lanthanum sulfate;
[0015] The molar concentration of the alcohol solution of the lanthanum salt is 0.15-0.55 mol / L, and the volume ratio of the mass of the carbon aerogel to the alcohol solution of the lanthanum salt is 1 g:8-12 mL.
[0016] Preferably, the immersion temperature is 20-30° C. and the immersion time is 12-16 hours.
[0017] Preferably, the calcination temperature is 300-600° C., and the heating rate to the required calcination temperature is 1-6° C. / min; the calcination holding time is 1.5-2.5 h.
[0018] The present invention also provides the use of the adsorption material described in the above technical solution or the adsorption material prepared by the preparation method described in the above technical solution as a dephosphorus adsorbent.
[0019] The adsorption material provided by the present invention comprises a carbon aerogel and a porous network formed in situ on the surface and / or in the pores of the carbon aerogel, wherein the porous network component is La 2 O 2 CO 3 In the present invention, La 2 O 2 CO 3 It has a three-dimensional porous network structure and contains abundant exchangeable anions and positively charged metal ions as adsorption sites, which can efficiently and quickly adsorb phosphorus. 2 O 2 CO 3 Medium CO 3 2- PO in wastewater 4 3-Ligand exchange is performed to achieve the purpose of phosphate adsorption. The adsorption material provided by the present invention has a high adsorption capacity and a fast adsorption rate for phosphorus in wastewater, with an adsorption capacity of 78.4-150.9 mg / g and a removal rate of 99.7% within 25 minutes. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the XRD spectrum of the adsorption material prepared in Example 1;
[0021] Figure 2 This is a SEM image of the adsorption material prepared in Example 1;
[0022] Figure 3 This is a SEM image of the adsorption material prepared in Example 2;
[0023] Figure 4 This is a TEM image of the adsorption material prepared in Example 1;
[0024] Figure 5 It is a bar chart comparing the adsorption capacity of phosphorus by the adsorption materials prepared in Example 1 and Comparative Examples 1 to 3;
[0025] Figure 6 It is a dot-line graph of the phosphorus removal rate of the adsorption material prepared in Example 1 at different adsorption times;
[0026] Figure 7 It is a bar chart comparing the adsorption capacity of phosphorus by the adsorption materials prepared in Example 1 and Examples 3 to 6. DETAILED DESCRIPTION
[0027] The present invention provides an adsorption material, comprising a carbon aerogel and a porous network formed in situ on the surface and / or in the pores of the carbon aerogel, wherein the porous network component is La 2 O 2 CO 3 and carbon.
[0028] In the present invention, the La 2 O 2 CO 3 The mass percentage of La in the adsorbent material is preferably 40-80%, more preferably 50-60%. In the present invention, the pore size of the porous network is preferably 10-20 nm, more preferably 15-17 nm. In the present invention, the adsorbent material has a larger pore size to facilitate the adsorption of phosphate in wastewater.
[0029] The present invention also provides a method for preparing the adsorbent material described in the above technical solution, comprising the following steps:
[0030] The biomass raw material is hydrothermally carbonized to obtain a biochar hydrogel;
[0031] The biochar hydrogel is subjected to vacuum freeze drying to obtain a carbon aerogel;
[0032] The carbon aerogel is immersed in an alcohol solution of a lanthanum salt for adsorption and then calcined to obtain the adsorption material.
[0033] The present invention hydrothermally carbonizes the biomass raw material to obtain a hydrogel of biochar. In the present invention, the water content of the biomass raw material is preferably 30-80%, more preferably 50-60%. In the present invention, the biomass raw material preferably includes peel, more preferably watermelon peel, grapefruit peel or cantaloupe peel. In the present invention, the hydrothermal carbonization preferably further includes: washing the biomass raw material. The present invention removes impurities such as sludge attached to the surface of the biomass raw material through washing.
[0034] In the present invention, the temperature of the hydrothermal carbonization is preferably 170-190°C, more preferably 180°C; the time of the hydrothermal carbonization is preferably 10-14h, more preferably 12-13h. In the present invention, the hydrothermal carbonization is preferably carried out in a polytetrafluoroethylene reactor lining.
[0035] In the present invention, after the hydrothermal carbonization, it is preferred that the method further comprises: immersing the system after the hydrothermal carbonization in an ethanol aqueous solution for impurity removal. In the present invention, the volume concentration of the ethanol aqueous solution is preferably 40-80%, more preferably 50-60%. The present invention can remove impurities such as soluble salts generated during the hydrothermal carbonization process through immersion. The present invention has no special requirements for the amount of the ethanol aqueous solution, the immersion time and the number of immersions, as long as the impurities in the system after the hydrothermal carbonization can be removed. In the present invention, the pH value of the immersion system after impurity removal is preferably neutral. In the present invention, after the immersion, it is preferred that the method further comprises: performing solid-liquid separation on the immersed system to obtain a hydrogel of biochar. In the present invention, the solid-liquid separation is preferably filtration. The present invention has no special requirements for the filtration, and the conventional method in the art can be used.
[0036] After obtaining the biochar hydrogel, the present invention vacuum freeze-dries the biochar hydrogel to obtain carbon aerogel. In the present invention, the vacuum degree of the vacuum freeze-drying is preferably 5 to 15 Pa, more preferably 5 to 10 Pa; the temperature of the vacuum freeze-drying is preferably -60 to -40°C, more preferably -45 to -55°C; the time of the vacuum freeze-drying is preferably 24 to 72 hours, more preferably 30 to 60 hours. The vacuum freeze-drying method used in the present invention can avoid the collapse of the carbon aerogel structure. In the present invention, the carbon aerogel is preferably brown.
[0037] In the present invention, the biochar hydrogel prepared by hydrothermal carbonization of biomass raw materials is subjected to vacuum freeze drying to obtain a carbon aerogel with a certain pore size, which is beneficial to improving the adsorption and dispersion of lanthanum, thereby improving the adsorption performance of the adsorption material.
[0038] After obtaining the carbon aerogel, the present invention immerses the carbon aerogel in an alcohol solution of a lanthanum salt for adsorption and then calcines to obtain the adsorption material. In the present invention, the lanthanum salt preferably includes hydrated lanthanum nitrate, hydrated lanthanum chloride, hydrated lanthanum carbonate or hydrated lanthanum sulfate, and more preferably hydrated lanthanum nitrate. In the present invention, the solvent in the alcohol solution of the lanthanum salt is preferably ethanol or methanol, and more preferably ethanol. The present invention uses alcohol compounds as solvents to enable the alcohol hydroxyl groups to fully combine with the carbon aerogel material during the impregnation process, so that the lanthanum ions are evenly dispersed on the surface and pores of the carbon aerogel. In the present invention, the molar concentration of the alcohol solution of the lanthanum salt is preferably 0.15-0.55 mol / L, and more preferably 0.35-0.45 mol / L; the mass of the carbon aerogel and the volume ratio of the alcohol solution of the lanthanum salt are preferably 1g:8-12mL, and more preferably 1g:9-10mL. The present invention limits the molar concentration of the alcohol solution of the lanthanum salt to the above range, which is used to form the best porous structure and La 2 O 2 CO 3 The monoclinic crystal structure improves the phosphate adsorption performance.
[0039] In the present invention, the immersion temperature is preferably 20 to 30° C., more preferably 23 to 25° C.; the immersion time is preferably 12 to 16 hours, more preferably 13 to 15 hours.
[0040] In the present invention, after the impregnation, the step preferably further includes: volatilizing the solvent in the impregnation system, and calcining the solid obtained after the solvent volatilization. The present invention has no special requirements for the solvent volatilization, and a conventional volatilization method in the art can be used, such as natural volatilization.
[0041] In the present invention, the calcination temperature is preferably 300-600°C, more preferably 400-500°C; the heating rate to the desired calcination temperature is preferably 1-6°C / min, more preferably 2-4°C / min; the calcination holding time is preferably 1.5-2.5h, more preferably 2h. In the present invention, the calcination is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably a nitrogen atmosphere.
[0042] In the present invention, the carbon aerogel material generated by hydrothermal carbonization and vacuum freeze drying of biomass raw materials has a porous structure, which allows lanthanum ions to enter and diffuse rapidly. Since the surface of the carbon aerogel is rich in negatively charged groups (hydroxyl, carboxyl, etc.), the lanthanum ions can be effectively anchored, which is conducive to the dispersion of the lanthanum element. In the subsequent calcination process, the porous structure of the carbon aerogel material will be destroyed, and the lanthanum salt and the carbon aerogel will interact to generate La 2 O 2 CO 3 And La 2 O 2 CO 3 In addition, the carbonyl groups present in large quantities on the surface of carbon aerogels also become La 2 O 2 CO 3 Medium CO 3 2- The origin of the formation. 2 O 2 CO 3 Medium CO 3 2- PO in wastewater 4 3- Ligand exchange is carried out to achieve the purpose of phosphate adsorption.
[0043] The present invention also provides the use of the adsorbent material described in the above technical solution or the adsorbent material prepared by the preparation method described in the above technical solution as a dephosphorization adsorbent. In the present invention, the method for dephosphorizing wastewater using the adsorbent material as a dephosphorization adsorbent preferably comprises the following steps:
[0044] The adsorption material is placed in phosphorus-containing wastewater for adsorption and phosphorus removal.
[0045] In the present invention, the phosphorus concentration in the phosphorus-containing wastewater is preferably 1-50 mg / L, more preferably 5-30 mg / L; the ratio of the mass of the adsorbent material to the volume of the phosphorus-containing wastewater is preferably 50-400 mg:1 L, more preferably 100-200 mg:1 L. In the present invention, the time for the adsorption and phosphorus removal is preferably 0.5-300 min, more preferably 1-30 min.
[0046] The adsorption material provided by the present invention has high selectivity for phosphate and good regeneration performance, and has good application prospects in water purification.
[0047] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] Example 1
[0049] The surface of the discarded watermelon rind with a water content of 50% was cleaned and placed in a polytetrafluoroethylene reactor lining, and then hydrothermally carbonized at 180°C for 12 hours, and then soaked in a 50% ethanol aqueous solution to remove impurities (the pH value of the system was 7 after soaking 7 times), and the biochar hydrogel was obtained after filtration;
[0050] The biochar hydrogel was freeze-dried at a vacuum degree of 10 Pa and a temperature of -50°C for 50 h to obtain a carbon aerogel material;
[0051] 1 g of carbon aerogel material was immersed in 10 mL of ethanol solution of hydrated lanthanum nitrate with a molar concentration of 0.35 mol / L at 25°C for 16 hours, and the solution was allowed to evaporate naturally; the solid obtained after volatilization was heated to 450°C in a tubular furnace in a nitrogen atmosphere at a heating rate of 2°C / min and calcined for 2 hours to obtain an adsorption material.
[0052] Example 2
[0053] The adsorption material was prepared according to the method of Example 1, except that the watermelon peel was replaced by grapefruit peel with a moisture content of 30%.
[0054] Example 3
[0055] The adsorption material was prepared according to the method of Example 1, except that the molar concentration of the ethanol solution of hydrated lanthanum nitrate was replaced from 0.35 mol / L to 0.15 mol / L.
[0056] Example 4
[0057] The adsorption material was prepared according to the method of Example 1, except that the molar concentration of the ethanol solution of hydrated lanthanum nitrate was replaced from 0.35 mol / L to 0.25 mol / L.
[0058] Example 5
[0059] The adsorption material was prepared according to the method of Example 1, except that the molar concentration of the ethanol solution of hydrated lanthanum nitrate was replaced from 0.35 mol / L to 0.45 mol / L.
[0060] Example 6
[0061] The adsorption material was prepared according to the method of Example 1, except that the molar concentration of the ethanol solution of hydrated lanthanum nitrate was replaced from 0.35 mol / L to 0.55 mol / L.
[0062] Comparative Example 1
[0063] 1 g of hydrated lanthanum nitrate was heated to 450° C. at a heating rate of 2° C. / min in a tubular furnace under a nitrogen atmosphere and calcined for 2 h to obtain an adsorption material free of carbon aerogel.
[0064] Comparative Example 2
[0065] The surface of the discarded watermelon rind was cleaned and then placed in a polytetrafluoroethylene reactor lining, and then hydrothermally carbonized at 180°C for 12 hours, and then immersed in a 50% ethanol aqueous solution to remove impurities, and then filtered to obtain a biochar hydrogel;
[0066] The biochar hydrogel was freeze-dried at a vacuum degree of 10 Pa and a temperature of -50°C for 50 h to obtain a carbon aerogel material;
[0067] 0.3 g of carbon aerogel material was heated to 450° C. at a heating rate of 2° C. / min in a tubular furnace in a nitrogen atmosphere and calcined for 2 h to obtain an adsorption material free of lanthanum.
[0068] Comparative Example 3
[0069] The adsorption material was prepared according to the method of Example 1, except that the carbon aerogel material was replaced by a commercial activated carbon material.
[0070] The adsorbent material prepared in Example 1 was subjected to X-ray diffraction detection to obtain an XRD spectrum, as shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the lanthanum in the adsorption material provided by the present invention is in the monoclinic phase La 2 O 2 CO 3 The adsorption materials prepared in Example 1 and Example 2 were examined by scanning electron microscopy to obtain SEM images, as shown in FIG. Figures 2-3 As shown, Figure 2 This is the SEM image of the adsorption material prepared in Example 1. Figure 3 The SEM image of the adsorbent material prepared in Example 2. The adsorbent material prepared in Example 1 was tested by transmission electron microscopy to obtain a TEM image, as shown in FIG. Figure 4 As shown. Figures 2 to 4 It can be seen that the adsorbent material has a three-dimensional porous network structure.
[0071] The adsorption materials prepared in Example 1 and Examples 3 to 6 were subjected to nitrogen physical adsorption and desorption tests to obtain pore data, which are listed in Table 1.
[0072] Table 1 Pore data of different adsorption materials
[0073] Example <![CDATA[BET specific surface area (m 2 / g)]]> Pore size (nm) Pore volume (cm3 / g) Example 1 28.7 16.7 0.093 Example 3 5.46 12.7 0.011 Example 4 7.61 15.5 0.017 Example 5 23.6 11.7 0.061 Example 6 21.7 14.6 0.063
[0074] 5 mg of the adsorbent materials prepared in Example 1 and Comparative Examples 1 to 3 were placed in a 100 mL beaker, and 50 mL of a 50 mg / L phosphorus concentration (in terms of KH 2 PO4 Phosphorus-containing aqueous solution (KH 2 PO 4 The solution was mixed and adsorbed for 240 minutes, and the concentration of P in the solution was measured by sampling. The adsorption capacity of the above materials for phosphorus (in terms of phosphorus) was calculated. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that the adsorption material provided by the present invention has excellent adsorption performance for phosphorus.
[0075] The adsorbent materials prepared in Examples 1, 4, 5 and Comparative Example 1 were immersed in KH2O with a P concentration of 10 mg / L at a dosage of 0.1 g / L. 2 PO 4 The adsorption was carried out in the standard solution at room temperature (25°C). Samples were taken every 1 min, 3 min, 5 min, 8 min, 10 min, 13 min, 15 min, 18 min, 20 min and 25 min, and the phosphorus concentration was determined by molybdenum blue spectrophotometry (Chinese Standard GB 11893-89). The test results (in terms of P) are listed in Table 2.
[0076] Table 2 Phosphorus removal rate of adsorption materials at different adsorption times
[0077]
[0078] According to Table 2, a dotted line graph of the phosphorus removal rate of the adsorption material prepared in Example 1 at different adsorption times is drawn, as shown in FIG. Figure 6 Combining Table 2 and Figure 6 It can be seen that the adsorption material provided by the present invention has good phosphorus removal performance and can achieve a removal rate of 99.7% within 25 minutes.
[0079] After microwave digestion of the adsorbent material of Example 1 (the digestion solution was a mixture of 5 mL of 50% nitric acid solution and 1 mL of 30% hydrogen peroxide solution; the digestion temperature was 150° C.; the digestion time was 30 min), the La element content was detected by ICP. The results showed that the mass of the La element accounted for about 60% of the total mass of the adsorbent material, and the calculated molar ratio of phosphorus to lanthanum was about 1.2, indicating that the utilization rate of lanthanum atoms was extremely high.
[0080] 5 mg of the adsorbent materials prepared in Example 1 and Examples 3 to 6 were placed in 100 mL beakers, and 50 mL of a 50 mg / L phosphorus concentration (in the form of KH 2 PO 4 Phosphorus-containing aqueous solution (KH 2 PO 4 The solution was mixed and adsorbed for 240 minutes, and samples were taken to determine the concentration of P in the solution. The adsorption capacity of the above materials for phosphorus (in terms of phosphorus) was calculated. The results are listed in Table 3.
[0081] Table 3 Phosphorus adsorption capacity of the adsorbent materials prepared in Example 1 and Examples 3 to 6
[0082] Example Example 1 Example 3 Example 4 Example 5 Example 6 Adsorption capacity (mg / g) 150.9 78.4 110.5 134.9 123.2
[0083] According to Table 3, a columnar comparison chart of the adsorption capacity of phosphorus by different adsorption materials is drawn, such as Figure 7 Combining Table 3 and Figure 7 It can be seen that the adsorption material provided by the present invention has a high adsorption capacity for phosphorus, and as the lanthanum concentration in the adsorption material increases, the adsorption capacity first increases and then decreases. The present invention can regulate the adsorption performance of the adsorption material for phosphorus by adjusting the lanthanum content in the adsorption material.
[0084] 5 mg of the adsorbent material prepared in Example 1 was placed in a 100 mL beaker, and 50 mL of a 50 mg / L phosphorus concentration (in the form of KH 2 PO 4 The phosphorus solution contains different anions Cl at a concentration of 50 mg / L or 200 mg / L (in terms of anions). - 、SO 4 2- 、NO 3 - , CO 3 2- After 240 minutes of adsorption, samples were taken to determine the concentration of P in the solution, and the adsorption capacity of the above materials for phosphorus (in terms of phosphorus) was calculated. The results are shown in Table 4.
[0085] Table 4 Selectivity of adsorbent material prepared in Example 1 for phosphate
[0086]
[0087] It can be seen from Table 4 that when phosphate and other anion salts coexist, the adsorbent material prepared in Example 1 still maintains a relatively high adsorption capacity for phosphorus, which indicates that the adsorbent material prepared in Example 1 has a relatively high selectivity for the adsorption of phosphorus.
[0088] The present invention uses different waste biomass as raw materials to prepare carbon aerogels, and forms a phosphorus removal carbon material with a three-dimensional porous network structure through the synergistic pyrolysis of lanthanum salt and carbon aerogels; and has excellent phosphorus removal performance. The raw materials for preparing the adsorption material in the present invention are cheap and easy to obtain, and the synthesis method is simple, green and has strong universality.
[0089] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An adsorption material, characterized in that: It comprises a carbon aerogel and a porous network formed in situ on the surface and / or in the pores of the carbon aerogel, wherein the components of the porous network are La2O2CO3 and carbon; The preparation method of the adsorbent material comprises the following steps: The biomass raw material is hydrothermally carbonized to obtain a biochar hydrogel; The biochar hydrogel is subjected to vacuum freeze drying to obtain a carbon aerogel; The carbon aerogel is immersed in an alcohol solution of a lanthanum salt for adsorption and then calcined to obtain the adsorption material.
2. The adsorption material according to claim 1, characterized in that: The mass percentage of La in the La2O2CO3 in the adsorption material is 40-80%.
3. The adsorption material according to claim 1 or 2, characterized in that: The pore size of the porous network is 10-20 nm.
4. The method for preparing the adsorbent material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The biomass raw material is hydrothermally carbonized to obtain a biochar hydrogel; The biochar hydrogel is subjected to vacuum freeze drying to obtain a carbon aerogel; The carbon aerogel is immersed in an alcohol solution of a lanthanum salt for adsorption and then calcined to obtain the adsorption material.
5. The preparation method according to claim 4, characterized in that: The biomass raw material includes peel; The temperature of the hydrothermal carbonization is 170-190° C., and the time is 10-14 hours.
6. The preparation method according to claim 4, characterized in that: The vacuum degree of the vacuum freeze drying is 5-15 Pa; the temperature of the vacuum freeze drying is -60--40° C.; and the time of the vacuum freeze drying is 24-72 hours.
7. The preparation method according to claim 4, characterized in that: The lanthanum salt includes hydrated lanthanum nitrate, hydrated lanthanum chloride, hydrated lanthanum carbonate or hydrated lanthanum sulfate; The molar concentration of the alcohol solution of the lanthanum salt is 0.15-0.55 mol / L, and the volume ratio of the mass of the carbon aerogel to the alcohol solution of the lanthanum salt is 1 g:8-12 mL.
8. The preparation method according to claim 4, characterized in that: The immersion temperature is 20-30° C. and the immersion time is 12-16 hours.
9. The preparation method according to claim 4, characterized in that: The calcination temperature is 300-600° C., and the heating rate to the required calcination temperature is 1-6° C. / min; the calcination holding time is 1.5-2.5h.
10. Use of the adsorption material according to any one of claims 1 to 3 or the adsorption material prepared by the preparation method according to any one of claims 4 to 9 as a dephosphorus adsorbent.
Citation Information
Patent Citations
Rare earth compositions and structures for removing phosphates from water
AU2008200837A1
Preparation method and applications of magnetic recyclable lanthanum oxycarbonate phosphorus-removal adsorbent
CN110694583A
Preparation method of composite phosphorus removal adsorbent lanthanum oxycarbonate loading montmorillonite
CN111744454A
Biochar aerogel material as well as preparation method and application thereof
CN113559797A
Lanthanum oxycarbonate catalyst as well as preparation method and application thereof
CN113797949A
